The Impact of Tax Incentives, Political Costs, Litigation Risk and Equity Valuation on Accounting Conservatism - Rahmat Novari; Yusnaini; Luk Luk Fuadah (Облік і фінанси, 2021)
In Indonesia, as in other countries, according to the requirements of the tax authorities, there is a need for reconciliation to match accounting profit and fiscal profit. Some rules are allowed in accounting standards but not in taxation. In reducing losses, the company must provide evidence of transparent financial statements that prioritize conservatism. Accounting conservatism is a set of bookkeeping guidelines that call for a high degree of verification before a company can make a legal claim to any profit. The general concept is to factor in the worst-case scenario of a firm’s financial future. The authors of this study attempt to assess the level of accounting conservatism based on several factors, namely through tax incentives, political costs, litigation risk, and equity valuation The purpose of this study is the analysis of the impact of tax incentives, political costs, litigation risk, and equity valuation on accounting conservatism. The secondary data used in this study are financial reports and annual reports published on the Indonesia Stock Exchange (IDX, www.idx.co.id) for 2015-2020. The sample of this study is manufacturing companies listed on the Indonesia Stock Exchange. Based on the criteria that have been determined using the purposive sampling method, there are 23 manufacturing companies. The results show that tax incentives and equity valuation have a positive and significant effect on accounting conservatism in manufacturing sector companies in Indonesia. Instead, factors such as political costs and litigation risk negatively affect accounting conservatism.